Global Pathway Analysis: a hierarchical framework to understand complex chemical kinetics. Issue 3 (4th May 2019) - Gao, Xiang; Gou, Xiaolong; Sun, Wenting
Abstract : An automated hierarchical framework, Global Pathway Analysis (GPA), is presented to understand complex chemical kinetics. The behaviour of the reacting system at macro level is bridged to the elementary reaction level by Global Pathways, which are the chemical pathways from an initial reactant species to a final product species. For each Global Pathway, its dominancy and effect on the system, such as those on the production or consumption of radicals, are quantified to understand its contribution to the system. Four examples are presented as demonstration: First, the classical second explosion limit of hydrogen is found to be resulted from the change of dominancy of a pressure-dependent Global Pathway, which consumes radical via H + O2 + M = HO2 + M reaction. Next, it is found that the negative temperature coefficient (NTC) regime of n-heptane is resulted from the competition between a low-temperature Global Pathway and a high-temperature Global Pathway. Third, a non-monotonic relation between autoignition delays and toluene ratio in toluene/ n -decane mixture is analysed. This automated framework has been placed in public domain. Reduced kinetic models can be generated based on Global Pathways too. Finally, this methodology is demonstrated using DNS simulation results of the extinction and re-ignition of a turbulent non-premixed flame. The differences between simulation results are investigated using two different kinetics models via the analysis of global pathways.